Prevalence of sexual initiation and associated factors in late adolescence: A study in selected tertiary level institutions in Malaysia / Shazimah Abdul Samad - Shazimah , Abdul Samad (2016)
The purpose of this study was to determine the psychometric properties of the Susceptibility to Peer Pressure Scale as well as the prevalence of sexual initiation and its risk factors among late adolescents attending tertiary level institutions. The temporal gap which exists between the maturation of the adolescents’ prefrontal cortex and their socio-emotional system predisposes them to engage in sexual initiation. The newly discovered independence that is associated with college environment further increases the propensity among late adolescents to initiate sexual intercourse. As this behaviour may result in negative consequences, such as unintended pregnancy, unsafe abortion or sexually transmitted infections, it is important to identify the crux of the matter in enabling the design and the implementation of risk reduction strategies. This study was conducted in two phases. Phase I comprised the establishment of the psychometric properties and the factorial invariance across gender of the Susceptibility to Peer Pressure Scale, one of the instruments used in Phase II. Both exploratory and confirmatory factor analyses were utilized. A cross-sectional study, employing a multistage stratified sampling method was conducted to establish the prevalence of sexual initiation and other related sexual behaviours as well as the correlates of engagement in sexual initiation in Phase II. A self-administered questionnaire based on adaptation of the Urie Bronfenbrenner’s social-ecological model which comprised several instruments to assess the characteristics of individual’s, familial and peer characteristics as well as school engagement was utilized. The correlates of sexual initiation were determined via multivariate logistic regression analyses adjusting for complex samples. A total of 1652 unmarried adolescents aged 18 and 19 years from six public and private institutions of higher learning in the Central region of Malaysia participated in this study. Overall, the Malaysian version of the Susceptibility to Peer Pressure Scale displayed good psychometric properties in terms of its construct validity, internal consistency and test-retest reliability in measuring iv susceptibility to peer pressure. Multi-group confirmatory factor analyses established the invariance of this scale across gender. The prevalence of sexual initiation among late adolescents was 9.8% (95% CI [8.3, 11.6]) with males reporting a higher rate of sexual engagement. Higher likelihood of sexual initiation was associated with perception of close friends have had sex, higher susceptibility to peer pressure and living in non-intact families among males and females. However, some gender differences were identified. As for males, Malays, current smokers, lifetime alcohol consumers, lifetime illicit drug use, early puberty, involvement in a relationship, and higher peer attachment were associated with sexual initiation. Sexual engagement among females, on the other hand, was linked to lifetime cigarette use and higher self-esteem. Females who reported higher religiosity and higher peer attachment were less likely to engage in sexual intercourse. The established risk factors originated from the elements of the adolescents’ immediate environment and their interactions. Thus, risk reduction strategies should conflate these elements in securing better outcomes. It is imperative to tailor these strategies based on gender differences. Future studies should contemplate qualitative research in exploring these risk factors.